PCB Waste Brake Pad - Che Mohd Ruzaidi, Ghazali, Assoc. Prof.; Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr.; Shamsul Baharin, Jamaludin, Prof. Dr.; Radzi Ali, Mohamed Faisol (Universiti Teknologi MARA, Kedah, 2010)
Invention, Innovation & Design (IID Kedah 2010), 28th - 29th July 2010 organized by Research & Industrial Linkages Division, Universiti Teknologi MARA (UiTM), Kedah at SP Inn, Kedah.